DAMPAK PEMEKARAN DESA TERHADAP PEMBANGUNAN INFRASTRUKTUR DI DESA KAPU JAYA KECAMATAN PALANGGA KABUPATEN KONAWE SELATAN - Mudana, Made; Nempung, Tibertius; Millia, Heppi (JURNAL EKONOMI UHO, 2016)
This study aims to evaluate the impact of regional expansion on infrastructure development in Kapu Jaya Village. The primary data obtained through interviews of head of village, and questionare to 60 respondent. The analytical method is used descriptive analysis. The results showed that regional expansion in Kapu Jaya Village have positive impact in infrastructure development. About 80 percent respondent assume that regional expansion improve availability in roads and infrastructure, health care facilities, medical personnel, medicines, and education.